Analisis Pengaruh Kualitas Website Terhadap Kepuasan Pelanggan Mister Aladin Dengan Menggunakan Webqual 4.0 - Rizka Amalia Kurniawati; Ari Kusyanti; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-commerce is an online market which has develop rapidly and has changed the business pattern by using internet as the useful communication tool. Mister Aladin is one of e-commerce in form of booking hotels site under MNC Media Investment Group. As one of the new e-commerce, it needs an evaluation to evaluate the factors which could affect customers' satisfaction while they accessed Mister Aladin. To evaluate customers' satisfaction, service quality become the main focus which affect customers' satisfaction. Some of researchers argue that the higher the quality, the more customers will get satisfied. To evaluate customer's satisfaction, it needs an accurate method and tool like WebQual 4.0. Based on this problem, this research focus on the effect of website quality toward customers' satisfaction. After doing the test from the evaluation of Mister Aladin's customers using WebQual 4.0, the data will be analyzed using linear regression analytics. As a result, website quality which consist of usability, information quality and service interaction quality is significantly affect customers' satisfaction of Mister Aladin. The effect of the quality which given by Mister Aladin will affect customers' satisfaction. As shown from the positive relation between independent variabel and user satisfaction variable.